Education to The Community About Understanding and Preventing Acute Respiratory Infections (ARI's) in Pagar Jati Community Health Center - Angriawan; Wati, Indah; Harahap, Fitri Ramadani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Acute respiratory infection (ARIs) are a global Health problems that affects society at large. ARi is the fourth leading cause of death in the population of all ages. According to North Sumatra Central Statistics Agency, ARI cases are the 4th highest disease in 2021. One causes of the high incidence of ARI is due to a lack of knowledge about ARI. This is caused by ignorance of ARI socialization, how to prevent ARI, and how to deal with ARI. The spread of ISPA can be prevented with a better understanding of risk factors, prevention and management. Community service is the key in efforts to spread knowledge about ISPA. This research explores the role of community service in increasing awareness of ISPA and encouraging preventive behavior among the community. Through outreach activities and public campaigns, community service has succeeded in increasing understanding of the importance of hand hygiene, vaccination, healthy respiratory practices and clean living habits in dealing with ISPA. Evaluation of the effectiveness of the community service program shows significant increase at the level of awareness, knowledge and preventive action against ISPA in the Pagar Jati Community Health Center. Collaboration between health workers, local government, educational institutions and the community are the main fondations for success this program. Although challenges such as limited access and information inequality still exist, community service has proven to be an effective instrument in strengthening community responses to ISPA as well as promoting overall community health.